2019
DOI: 10.1039/c9sc03389k
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule dynamic DNA junctions for engineering robust molecular switches

Abstract: Highly robust DNA molecule switches were engineered by utilizing single-molecule dynamic three-way junctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The stimulus-responsive assembly of Y-shaped DNA is mainly motivated by the static or dynamic self-assembly approach . The traditional static self-assembly represents a simple way to obtain a Y-shaped DNA construct yet is constrained with limited sensitivity for each analyte contributes to only one Y-shaped DNA unit . To resolve this obstruction, the static self-assembly of Y-shaped DNA is often integrated with protein enzymes to achieve a more sensitive analyte assay. However, these combined strategies are often confronted with the relatively complicated design and tedious enzyme modification procedures.…”
mentioning
confidence: 99%
“…The stimulus-responsive assembly of Y-shaped DNA is mainly motivated by the static or dynamic self-assembly approach . The traditional static self-assembly represents a simple way to obtain a Y-shaped DNA construct yet is constrained with limited sensitivity for each analyte contributes to only one Y-shaped DNA unit . To resolve this obstruction, the static self-assembly of Y-shaped DNA is often integrated with protein enzymes to achieve a more sensitive analyte assay. However, these combined strategies are often confronted with the relatively complicated design and tedious enzyme modification procedures.…”
mentioning
confidence: 99%
“…A DNA navigator operating at a single-molecule level can be used in solving mazes by real-time tracking of the reaction path . A recent study demonstrated a robust molecular switch engineered by single-molecule dynamic DNA junctions . Due to the real-time tracking techniques at the single-molecule level, the kinetics-based outputs or the leakage can be distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…22 A recent study demonstrated a robust molecular switch engineered by single-molecule dynamic DNA junctions. 23 Due to the real-time tracking techniques at the single-molecule level, the kinetics-based outputs or the leakage can be distinguished. Hence, an investigation of the single-molecule methods could bring special advantages to detecting and measuring DNA computing.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are several technologies available for nucleic acid detection and analysis such as hybridization, strand displacement, and enzymatic and nonenzymatic amplification assays. These techniques employ either single-molecule or ensemble approaches including optical, electrochemical, and colorimetric assays. , Although hybridization-based assays offer a simple and fast analysis of nucleic acid targets, they typically exhibit poor specificity between the target with perfect complementarity and the one with a point mutation. , Therefore, any sensing approach that is sensitive down to single-nucleotide mismatch can be a very useful attribute to ensure specificity of diagnosis. Although enzymatic amplification approaches such as polymerase chain reaction (PCR), reverse transcriptase PCR (RT-PCR), and digital PCR are simple and highly sensitive, they rely on target amplification and are susceptible to false negatives/positives. This is problematic because false negatives run the risk of instilling a false sense of security and false positives may result in unnecessary panic. Therefore, novel single-molecule and ensemble techniques including DNA nanotechnology platforms with improved sensitivity and specificity are continuously emerging in recent years. Nonetheless, most of these methods are rather complicated and have limited applications.…”
mentioning
confidence: 99%